An n-th order Lagrangian forward model for large-scale structure. Issue 4 (12th April 2021) - Schmidt, Fabian
Abstract: A forward model of matter and biased tracers at arbitrary order in Lagrangian perturbation theory (LPT) is presented. The forward model contains the complete LPT displacement field at any given order in perturbations, as well as all relevant bias operators at that order and leading order in derivatives. The construction is done for any expansion history and does not rely on the Einstein-de Sitter approximation. A large subset of higher-derivative bias operators is also included. As validation test, we compare the nLPT-predicted matter density field and that from N-body simulations using the same initial conditions. For simulations using a cutoff in the initial conditions, we find subpercent agreement up to scales of k ∼ 0.2 h -1 Mpc. We also find subpercent agreement with full simulations without cutoff, both for the power spectrum and nonlinear σ8 -inference, when allowing for the effective sound speed. The application to biased tracers (halos) has already been presented in a recent paper [1].